Ex vivo culture of malignant primary B cells - Canonne, Morgane; George, Fabienne; Graux, Carlos (Frontiers in Hematology, 2022)
Mature B cell malignancies constitute a wide range of biologically and clinically heterogeneous hematological diseases. Despite an increasingly thorough understanding of the physiopathology of these pathologies and significant improvements in therapies, a dismal outcome still affects a large number of patients. Therefore, further investigations into new treatment perspectives are highly needed and they depend entirely on the ex vivo culture of patient cells. Primary cells usually demand superior culture models, as they are notoriously difficult to cultivate. The literature is not devoid of approaches ranging from two- to three-dimensional systems for culturing mature malignant primary B cells. However, they display substantial protocol inter-variation. This imposes a high risk of failures, repeats, and inconsistent results, which are neither compatible with the rare value of primary cells nor the efficiency of the drug discovery process. In this review, we provide a thorough overview of the different approaches that have been implemented in the literature for the culture of mature malignant primary B cells, and we discuss associated considerations and limitations to assist researchers in determining a fit-for-purpose culture system, thereby attempting to reduce the number of trials and errors as well as associated biomaterial expenditure.